Tilang Elektronik (ETLE) sebagai Alat Pencegahan Tindak Pidana Pelanggaran Lalu Lintas Menurut Undang-Undang No 22 Tahun 2009 dan Maqāṣid al-Syarī’ah di Polres Tanjab Barat: Implementation of Electronic Ticketing (ETLE) as a Tool to Prevent Traffic Violation Criminal According to Law No. 22 of 2009 and Maqāṣid al-Syarī’ah at Tanjab Barat Police - Umar Wira Febriansyah, Umar Wira Febriansyah; Ruslan Abdul Gani; Rahmi Hidayati (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2025)
The purpose of this study is to investigate the use of Electronic Ticketing as a Tool to Prevent Traffic Violations According to Law No. 22 of 2009 and Maqashid Al-Syariah in the West Tanjung Jabung Police area. The background of this study is the high number of violations and road accidents that are still a problem in the area. Electronic ticketing-based law enforcement (ETLE) is an innovation to increase the effectiveness of supervision, reduce corrupt practices, and increase public awareness of traffic law. The method used in this study uses an empirical study methodology that uses legal sociology and legislative methodology, with primary data obtained through observation, interviews, and documentation in the West Tanjung Jabung Police area using the West Mobile platform. The results of the study indicate that the implementation of electronic ticketing in the West Tanjung Jabung Police was carried out through the stages of ETLE design, officer training, community outreach, implementation trials, and full implementation. This implementation has a positive impact on increasing traffic law awareness and reducing the number of violations. However, several obstacles remain, namely; limited infrastructure, low technological literacy of the community, and resistance to change. Efforts to overcome these obstacles are carried out through collaboration with local governments, improving facilities, and implementing ongoing socialization. A review of the Maqashid Al-Syariah perspective, in the implementation of ETLE using the principles of protecting life (hifdz al-nafs), property (hifdz al-mal), reason (hifdz al-‘aql), religion (hifdz al-din), and descendants (hifdz al-nasl) has not been running optimally, ETLE functions as an instrument to maintain public safety and uphold justice equally, in accordance with the values ​​of Islamic law.